Eugenol inhibits veratridine-induced non-convulsive seizures and wet dog shakes via blockage of sodium and calcium influx in rat cerebrocortical synaptosomes - Ransford Amoah, Priscilla Kolibea Mante, Nana Ofori Adomako, Paulina Antwi (Journal of Applied Pharmaceutical Science, 2021)
Studies have confirmed that the electroencephalogram (EEG) pattern produced by veratridine (VTD) administration is comparable to that seen in absence seizures, partial seizures, and epileptic encephalopathies. VTD has thus been considered a valuable epileptogenic agent for screening of antiepileptic agents. This study investigated the activity of eugenol (EUG) against VTD-induced seizures. Seizures were induced in Sprague-Dawley rats with VTD (400 μg/kg; i.p.) after implantation of electrodes for electroencephalogram recording. Animals were observed for seizure activity and the number of wet dog shakes (WDS). The number of WDS was significantly (p = 0.0141) reduced by pretreatment with EUG at 100 mg/kg. Animals experienced frequent quiescent periods with recorded epileptiform activity. Pretreatment with 400 mg/kg ethosuximide and 200 mg/kg valproic acid abolished spike activity. Pretreatment with EUG at 100 mg/kg was more effective against inhibition of spike activity. EUG also significantly (p = 0.0001) inhibited the influx of sodium and calcium ions in cerebrocortical synaptosomes from isolated rat brains. EUG inhibits VTD-induced nonconvulsive seizures and WDS in rats.
Keywords: Absence seizure, sodium channels, calcium channels, EEG, valproate